Managing the Current Customization of Process Related IT-Services - Brocke, H.; Uebernickel, F.; Brenner, W. (2010 43rd Hawaii International Conference on System Sciences, 2010)
IT service providers are increasingly required to orientate their service portfolio towards the IT support of their consumer's business processes. This enables diversification as well as transparency in costs and services vis-a-vis the customer to be achieved. Such services however, appear too customer specific for a standardized service provision within the context of IT-industrialisation as they are subject to constantly changing customer demands. To combat this, a concept is envisaged that keeps business process orientated IT-services modifiable and configurable by concretely defining additional Associate Services in advance. In order to maintain transparency and influence in IT expenses, these services orientate themselves towards business objects in the customer's business. The concept is illustrated with the aid of examples from its application and further development together with two associate IT-providers.